Hypertensive user’s adherence to treatment and the interface with knowledge about the disease - Lima, Helder de Pádua; Santos, Zélia Maria de Sousa Araújo; Nascimento, Jennara Cândido do; Caetano, Joselany Áfio (Rev Rene, 2010)
The aim of this work was to analyze the interface between hypertensive patients’ knowledge about hypertension and the adoption of therapeutic conducts to control the disease. It was a descriptive and exploratory study developed with 400 hypertensive users registered in the Arterial Hypertension League of the Hospital of Messejana – LHAHM in Fortaleza-CE, Brazil. The data were collected from July to October 2006, through interviews, using a structured script. The results show that most users were female (67.2%), mulatto (54.7%), between 50 and 79 years old (81.8%), and 54 (13.5%) were black. The users’ knowledge on systemic arterial hypertension was based on concepts related to their design and seriousness and most did not know about the chronic and asymptomatic nature. A significant association was found between knowledge on important therapeutic conducts and hypertensive patients’ adherence to treatment.